Handbook of Polish, Czech, and Slovak Holocaust Fiction Works and Contexts - Holý, Jiří; Nichtburgerová, Hana; Hiemer, Elisa-Maria; Firlej, Agata (De Gruyter Reference, 2021)
The Handbook presents literary fiction works on the Holocaust in three Slavic languages. It contains more than 120 articles including an introduction dealing with Holocaust literature in the broader context. The publication will become a standard reference book at universities and in public libraries, and will be useful to everyone interested in the Holocaust, anti-Semitism, World War II, and Jewish-related literature.